A mutation in the neonatal isoform of SCN2A causes neonatal‐onset epilepsy. Issue 3 (7th December 2021) - Penkl, Anja; Reunert, Janine; Debus, Otfried M.; Homann, Anna; Och, Ulrike; Rust, Stephan; Marquardt, Thorsten
Abstract: SCN2A (sodium channel 2A) encodes the Nav1.2 channel protein in excitatory neurons in the brain. Nav1.2 is a critical voltage‐gated sodium channel of the central nervous system. Mutations in SCN2A are responsible for a broad phenotypic spectrum ranging from autism and developmental delay to severe encephalopathy with neonatal or early infantile onset. SCN2A can be spliced into two different isoforms, a neonatal (6N) and an adult (6A) form. After birth, there is an equal or higher amount of the 6N isoform, protecting the brain from the increased neuronal excitability of the infantile brain. During postnatal development, 6N is gradually replaced by 6A. In an infant carrying the novel SCN2A mutation c.643G > A (p.Ala215Thr) only in the neonatal transcript, seizures started immediately after birth. The clinical presentation evolved from a burst‐suppression pattern with 30–50 tonic seizures per day to hypsarrhythmia. The first exome analysis, focusing only on common transcripts, missed the diagnosis and delayed early therapy. A reevaluation including all transcripts revealed the SCN2A variant.